2013
DOI: 10.1002/ejlt.201300157
|View full text |Cite
|
Sign up to set email alerts
|

Organic plant ingredients in the diet of Rainbow trout (Oncorhynchus mykiss): Impact on fish muscle composition and oxidative stability

Abstract: Rainbow trout were fed diets containing either fish meal and fish oil (FM-FO) (control) or diets in which 40% of the fishmeal was substituted with a mixture of ingredients grown organically including plant protein concentrate (PP) in combination with either fish oil (FO) as lipid source, or one of the following organic plant oils; rapeseed (RO), linseed/flaxseed (LO), grape seed (GO), or sunflower (SO). The impact of these substitutions was investigated by measuring fish muscle fatty acid profile as well as ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…As regards to long chain 3 PUFAs, precursors of eicosanoids and other lipid mediators, the major contributors were docosahexaenoic (DHA, 22:63), eicosapentaenoic (EPA, 20:53), and -linolenic (ALA, 18:33) acids. Their content agreed with the values proposed for farmed rainbow trout fed commercial feeds (Baron et al, 2013;Blanchet, Lucas, Julien, Morin, Gingras, & Dewailly, 2005;Haliloǧlu, Bayır, Necdet Sirkecioǧlu, Mevlüt Aras, & Atamanalp, 2004) containing both fish meal and fish oil. No differences were found between asphyxia and percussion groups.…”
Section: Muscle and Plasma Fatty Acidssupporting
confidence: 83%
See 1 more Smart Citation
“…As regards to long chain 3 PUFAs, precursors of eicosanoids and other lipid mediators, the major contributors were docosahexaenoic (DHA, 22:63), eicosapentaenoic (EPA, 20:53), and -linolenic (ALA, 18:33) acids. Their content agreed with the values proposed for farmed rainbow trout fed commercial feeds (Baron et al, 2013;Blanchet, Lucas, Julien, Morin, Gingras, & Dewailly, 2005;Haliloǧlu, Bayır, Necdet Sirkecioǧlu, Mevlüt Aras, & Atamanalp, 2004) containing both fish meal and fish oil. No differences were found between asphyxia and percussion groups.…”
Section: Muscle and Plasma Fatty Acidssupporting
confidence: 83%
“…PUFA represented the majority of total fatty acids in muscle, composed primarily by 6 and by a smaller amount of 3. Although a certain caution is required in the comparison of the results with previous studies, since the FA composition depends considerably on diets (Baron, Svendsen, Lund, JokuSEMn, Nielsen, & Jacobsen, 2013), the presence of vegetable sources in the feed for the farmed rainbow trout of the present trial is reflected mainly by the percentage of linoleic acid (18:26) that reached up 27 % of TFA. Linoleic acid is the precursor for the synthesis of arachidonic acid (ARA, 20:46) which was the third major component of the 6 fraction, providing 1% of TFAs in muscle.…”
Section: Muscle and Plasma Fatty Acidsmentioning
confidence: 80%
“…Aldehydes, such as hexanal, ( E , E )‐2,4‐heptadienal, octanal, nonanal, and so forth, ketones, and alcohols increased remarkably in puffer fish during cold storage and imparted a more characteristic fishy flavor (Guran, Oksuztepe, Coban, & Incili, ; Mahmoud & Buettner, ). In this study, the concentration of hexanal and octanal increased in the puffer fish during storage, which was expected as some aldehydes could be generated from lipid oxidation, for example, hexanal showed in much higher concentrations increase due to the oxidation of both linoleic and linolenic acid and is considered as a good marker for oxidation products of n‐3 and n‐6 fatty acids (Baron et al, ; Frank, Poole, Kirchhoff, & Forde, ). ( E , E )‐2,4‐Heptadienal is an off‐flavor compound and can be considered as a marker of lipid oxidation (Hwang et al, ).…”
Section: Resultsmentioning
confidence: 56%
“…These results are in agreement with previous studies in rainbow trout and Atlantic salmon, in which replacement of FO with VO reduced the formation of primary oxidation products such as lipid hydroperoxides (71) or TBARS (72) . Other studies have not found differences in oxidative stability in salmon muscle when FO was substituted by VO (43) , or they have found lower oxidation rates in VO-fed fish than in FO-fed ones (73) , which indicates that the presence of other antioxidant nutrients such as α-tocopherol or carotenoids may be more critical for oxidative stability in flesh than the degree of unsaturation of the feeds or Se levels in the flesh.…”
Section: Discussionmentioning
confidence: 95%